Effect of short chain branches distribution on fracture behavior of polyethylene pipe resins. (July 2018) - He, Xuelian; Zha, Xiaojuan; Zhu, Xiao; Qi, Xin; Liu, Boping
Abstract: In this paper, a series of unimodal and bimodal high density polyethylene (HDPE) pipe resins with the similar molecular weight distribution and low short chain branches (SCB) contents were investigated to discover the relationship between short chain branches distribution (SCBD) and fracture behaviors. Three characterization methods, namely temperature rising elution fractionation (TREF), high temperature gel permeation chromatography (HT-GPC) and self-annealing fraction (SSA), have been effectively combined to qualitatively analyze investigate the SCBD of HDPE pipe resins. The results showed the preference of incorporation of SCB into long chains caused the enhancement of yielding stress and strain hardening (SH) modulus, and thus the extension of rupture time. On one hand, this kind of SCB distribution is conductive to induce the nucleation of long chains and form more void volume in the neighborhood of long chains indicating faster migration speed of polymer chains. On the other hand, short chains with less SCBs are easy to rapidly occupy nearby sites on the crystal growth front of long chains to co-crystallize. Whereas, these HDPE resins with the more SCBs incorporated into short chains spent much longer time occupying the growth front, so that parts of these types of short chains form very thinner lamella differentiated from the main crystallizing region. During the initiation and propagation of craze, these parts were firstly broken and their resistance to slow crack growth was based on the incorporating degree of SCBs into short chains. Therefore, besides molecular weight distribution, SCBD is another main cause for long-term properties of HDPE pipe resins. Highlights: Three methods, TREF, HT-GPC and SSA, have been effectively combined to qualitatively analyze the SCBD of HDPE pipe resins. A lamellar model was proposed to disclose the relationship between SCB distributed on main chains and SCG resistance. The yielding stress and the SH modulus were tested to indicate the rupture time of HDPE pipe resins.